The Relationship of Socioeconomic Decline with the Incidence of Sexually Transmitted Infections (STIs) - Puguh Riyanto; Devina Adiyani Pranowo; Dini Hisan Wijdani; Cindy Cindy; Cagar Irwin Taufan Pamungkas (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Sexually transmitted infections (STIs) are a reproductive health problem closely associated with socioeconomic conditions. Economic downturns can hinder access to timely sexual health services, condoms, and treatment, potentially increasing vulnerability to STIs. Objective: This study aimed to evaluate the association between perceived socioeconomic decline and self-reported STI diagnosis among sexually active adults. Methods: This study used an analytical observational design with a cross-sectional approach. The subjects were sexually active adults who met the eligibility criteria. Data were collected using structured questionnaires assessing perceived economic decline, sexual history, and STI diagnosis status. The association between economic decline and STI occurrence was analyzed using the chi-square test, and the prevalence ratio (PR) with a 95% confidence interval (CI) was reported. Results: This study involved 92 subjects, with a mean age of 30.49 ± 6.00 years. The proportion of STIs in the group experiencing economic decline was 31.3%, whereas the proportion in the group without economic decline was 10.7%. Perceived economic decline was associated with STI prevalence (PR = 2.917; 95% CI: 0.943–9.023; p = 0.036), although the CI crossing 1.0 warrants cautious interpretation. Conclusion: Economic downturn was associated with the incidence of STIs. Further research is recommended using a prospective design with multivariate analysis and clinically confirmed STI diagnoses. These findings have implications for public health practice, particularly in designing STI prevention programs that integrate economic support components and address socioeconomic vulnerabilities. Health policymakers should consider incorporating STI screening and education into social protection programs targeting economically distressed populations.